Developing and mechanical properties of low fired and geopolymer bricks from drinking water sludge with different contents of added fly ash - Zulfahmi Ali Rahman; Aifahana Syamimie Mohd Suhaimi; Wan Mohd Razi Idris; Tukimat Lihan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Raw water treatment and coal-based power generation facilities produce a high level of waste to the environment annually. A low recycling scheme has worsened the situation and wastes usually end up in a landfill. Further environmental degradation could be prevented by re-utilising wastes for the production of alternative bricks. Additionally, the development of low-fired brick from wastes can comparatively reduce energy consumption during the firing stage. Geopolymer has successfully replaced ordinary portland cement (OPC) without bargaining its mechanical quality. This study aimed to investigate the effect of fly ash (FA) content and geopolymerization on mechanical characteristics of brick developed from drinking water sludge (DWS). A set of brick samples was fired at 500 oC while another set of samples was prepared under a high alkaline condition to produce geopolymer bricks. Resultantly, both sets of samples demonstrated a decrease in linear shrinkage and increased density with more content of FA. For fired brick samples, the water absorption decreased from 38.6% to 33.3% before rising again at 45% of FA content. However, a continuous decrease was displayed by geopolymer brick as FA increased. The compressive strength of fired bricks showed a decreasing trend as FA content increased and vice versa for the geopolymer brick. The compressive strength of geopolymer bricks increased from 1.22 MPa to 3.63 MPa at 45% of FA content. Comparatively, geopolymer bricks demonstrated higher strength than fired bricks. These results reflect the advantage of the incorporated wastes and geopolymerisation in developing alternative brick for sustainable resources and a better environment.